Are banks using hidden reserves to beat earnings benchmarks? Evidence from Germany - Bornemann, Sven; Kick, Thomas; Memmel, Christoph; Pfingsten, Andreas (Journal of Banking & Finance, 2012)
Section 340f of the German Commercial Code allows banks to provision against the special risks inherent to the banking business by building hidden reserves. Beyond risk provisioning, these reserves are implicitly accepted as an earnings management device. By analyzing financial statements of German banks for the period 1997–2009, we see these hidden reserves being used to (1) avoid a negative net income, (2) avoid a drop in net income compared to the previous year, (3) avoid a shortfall in net income compared to a peer group, and (4) reduce the variability of banks’ net income over time. Our analysis also shows that if bank managers are unable to reach the targets as set out in (1)–(3), they are more inclined to keep the hidden reserves for use in future periods.